The Interaction of Fiqh and Science in the Dynamics of Determining the Beginning of the Hijri Month in Indonesia - Muhammad Hasan (Journal of Islamic Law)
The determination of the onset of the Hijri month in Indonesia has frequently sparked controversy, especially among prominent Islamic organizations such as Nahdlatul Ulama and Muhammadiyah, as well as governmental entities like the Ministry of Religious Affairs. This contention arises from the diverse methods and criteria they adopt for the sighting of the hilāl (new crescent Moon) to mark the beginning of the Hijri month. This article delves into the interplay between fiqh (Islamic jurisprudence) and astronomy in determining the start of the Hijri month within the Indonesian context. Employing literature research with a scientific-cum-doctrinal approach, the article highlights three interactions between fiqh and science. Firstly, astronomy serves as a translator of jurisprudential concepts into empirical criteria for determining the beginning of the Hijri month. It underscores the interdependence of these two domains in decision-making rooted in religious beliefs and empirical knowledge. Secondly, the dynamic process of determining the start of the Hijri month in Indonesia reveals a complex interplay between fiqh and science, with varying viewpoints among religious scholars and scientific researchers regarding the criteria for moon sighting. Lastly, fiqh plays a role in legitimizing astronomy in the rukyah al-hilāl (crescent moon sightings) process through testimonies, wherein scholars of Islamic jurisprudence establish criteria for witnesses and use oaths to validate empirical scientific evidence supporting lunar visibility. This article offers valuable insights into the intricate relationship between fiqh and science in determining the start of the Hijri month in Indonesia.